Pengaruh Net Profit Margin dan Debt to Equity Ratio terhadap Harga Saham pada PT. Arwana Citramulia, Tbk - Yeti Kusmawati; Denok Sunarsi; Sudiarto Sudiarto; Ratna Dumilah (Prodi Akuntansi STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of Net Profit Margin and Debt to Equity Ratio on stock prices at PT. Arwana Citramulia, Tbk Period 2010-2019. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study Net Profit Margin has no significant effect on stock prices of 27.0%, hypothesis testing obtained a significance value (Sig.) 0.123 > 0.05. Debt to Equity Ratio has a significant effect on stock prices of 59.0%, hypothesis testing obtained a significance value (Sig.) 0.009 <0.05. Net Profit Margin and Debt to Equity Ratio simultaneously have a significant effect on stock prices with the regression equation Y = 781.144 + 19.436X1 - 8,776X2 and the contribution of the effect is 67.0%, hypothesis testing is obtained Significance value (Sig.) 0.021 < 0.05 .